Empathy Modulates the Effects of Acute Stress on Anxious Appearance and Social Behavior in Social Anxiety Disorder - von Dawans, Bernadette; Trueg, Amalie; Voncken, Marisol; Dziobek, Isabel; Kirschbaum, Clemens; Domes, Gregor; Heinrichs, Markus (Frontiers in Psychiatry, 2022)
Patients suffering from social anxiety disorder (SAD) fear social interaction and evaluation, which severely undermines their everyday life. There is evidence of increased prosocial behavior after acute social stress exposure in healthy individuals, which may be interpreted as stress-regulating ‘tend-and-befriend’ behavior. In a randomized controlled trial, we measured empathic abilities in a first diagnostic session. In the following experimental session, we investigated how patients with SAD (n=60) and healthy control participants (HC) (n= 52) respond to an acute social stressor (Trier Social Stress Test for groups) or a non-stressful control condition, and whether empathic abilities and acute social stress interact to modulate anxious appearance and social behavior in a social conversation test. Salivary cortisol, heart rate and subjective stress response were repeatedly measured. The anxious appearance and social behavior of participants were rated by the conversation partner. SAD patients demonstrated stronger subjective stress responses while the biological responses did not differ from HC. Moreover, patients performed worse overall in the conversation task, which stress stress impaired additionally. Finally, we found that both emotional and cognitive empathy buffered the negative effects of acute stress on social behavior in SAD, but not in HC. Our data highlight the importance of empathic abilities for SAD during stressful situations and call for multimodal clinical diagnostics. This may help to differentiate clinical subtypes and offer better-tailored treatment for patients.